Cancer in Iraq, general view of annual report 2022 - Salih, Hiba H.; Abd, Sura Y.; Al-Kaseer, Eman; Al-Diwan, Jawad (Journal of Contemporary Medical Sciences, 2024)
Objective: Increasing cancer rate in Iraq is a concerning issue. The rise in life expectancy, shift in behavior risk factors, and the effects of armed conflict may be contributing to this increase. This work was carried out to provide a review of cancer in Iraq. Methods: Data were obtained from cancer registration, cancer board in Iraq in Ministry of Health in Iraq for the years 1976 to 2022. Cancer incidence was calculated as case per 100000 population for each year. Population of Iraq was obtained from Ministry of Planning. Results: Incidence of cancer has generally increase through the time (upward trendline in incidence of cancer over years). The R2 suggests a reasonable capture in variation in the incidence of cancer. The age -standardized incidence rate of cancer in 2022 was 158.94 per 100000. Incidence rates were more prominent in Al-Najaf, Al-Sulaymaniyah, Erbil and Karbala (123.74, 121.4, 119.9 and 111.8 per 100 000, respectively). Conclusion: addressing the issue of cancer in Iraq requires a multifaceted approach that includes improving environmental conditions, enhancing healthcare services and raising awareness about cancer prevention and early detection.